Neutron Scaling Laws from Numerical Experiments - Lee, S.; Saw, S. H. (Springer US, 2008)
Experimental data of neutron yield Yn against pinch current Ipinch is assembled to produce a more global scaling law than available. From the data a mid-range point is obtained to calibrate the neutron production mechanism of the Lee Model code. This code is then used for numerical experiments on a range of focus devices to derive neutron scaling laws. The results are the following: Yn = 2 9 1011Ipinch 4.7 and Yn = 9 9 109Ipeak 3.9. It is felt that the scaling law with respect to Ipinch is rigorously obtained by these numerical experiments when compared with that obtained from measured data, which suffers from inadequacies in the measurements of Ipinch.